Effect of teachers’ asynchronous e-feedback and synchronous oral feedback on English language learners’ writing accuracy - Nusrat, Aasia; Khan, Sardaraz; Kashif, Farah; Fawad, Rakhshanda (Frontiers in Education, 2022)
This research aims to assess the efficacy of electronic feedback (e-feedback) and traditional oral feedback on undergraduate students’ English writing over 12 weeks of teaching. Three treatment groups were involved: Asynchronous written e-feedback through Microsoft Word Track Changes; teacher–student oral metalinguistic conferencing; no feedback control group. Two grammatical features (i.e. conjunctions and articles), the most problematic forms, were targeted to determine the effect of feedback on these grammatical features. One-way ANOVA test resulted to reveal that the feedback-receiving group performed better than those given no feedback at all. Furthermore, students who received e-feedback performed much better in improving conjunctions errors than those who received oral feedback. The study suggests to train learners and teachers towards e-feedback for better learning of English language.